Marine-Derived Astaxanthin: Molecular Mechanisms, Biomedical Applications, and Roles in Stem Cell Biology - Aretha Rambaldi; Francesca Paris; Pasquale Marrazzo; Roberta Costa; Stefano Ratti; Francesco Alviano (Marine Drugs)
Astaxanthin (ASX) is a xanthophyll carotenoid mainly derived from marine microalgae such as Haematococcus pluvialis and Chlorella zofingiensis, as well as the yeast Phaffia rhodozyma. Its chemical nature structure, rich in conjugated double bonds, carbonyl, and hydroxyl groups, confers potent antioxidant and anti-inflammatory properties. ASX modulates oxidative stress via the PI3K/Akt-Nrf2 pathway and suppresses NF-κB-mediated inflammatory responses, reducing cytokine levels such as TNF-α, IL-6, and iNOS. ASX exerts dual apoptotic effects, cytoprotective in non-transformed cells and pro-apoptotic in cancer cells through p53 activation. Sustainable extraction techniques, especially supercritical CO2, have improved its industrial applicability. Recent findings highlight ASX’s role in stem cell biology, enhancing proliferation, supporting lineage-specific differentiation, and protecting against oxidative and inflammatory damage, which is a crucial issue for regenerative medicine applications. These multifaceted molecular effects support ASX’s therapeutic potential in chronic diseases, including diabetes, cardiovascular pathologies, and cancer. This review outlines ASX’s natural sources, extraction methods, and biological mechanisms, emphasizing its application in oxidative stress- and inflammation-related conditions.